Evropski koncept neodvisnega sodstva in kvantifikacija formalne neodvisnosti sodstva v izbranih državah Evropske unije - Lipič Plohl, Danaja (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2022)
The authors discuss the European legal standards of an independent judiciary as contained in the Council of Europe’s documents and legal acts as well as in the case law of the European Court of Human Rights and the Court of Justice of the European Union. For the operationalisation of the European concept of independent judiciary, the authors developed a special test (questionnaire) included in the article’s appendix to enable the quantification of a formal judicial independence in selected countries, especially in the EU Member States. Based on the aforementioned test, the authors analysed the Croatian, Hungarian, German, Polish and Slovenian legal systems in the field of judiciary. They noted that systemic deficiencies exist in the Polish and Hungarian legal systems, which, according to the authors, fail to meet some of the fundamental European legal standards of an independent judiciary. On the other hand, however, they did not find such deficiencies in the Croatian, German and Slovenian legal systems. A comparison of the three legal systems shows differences in compatibility with individual legal standards, which consequently indicate that in each of the observed legal systems improvements are possible or in fact desirable. Overall, however, the legal systems of those three selected countries are comparable with one another, considering a measured score of around 0,8 (80 per cent) in all of them, which is sufficient enough to conclude that formal judicial independence in Croatia, Germany and Slovenia is guaranteed. Moreover, the authors paid special attention to cases that may at first glance appear to be consistent with the European concept of an independent judiciary, but in fact are not. In this regard, the authors pointed out a special body that is supposed to provide a kind of buffer zone between the legislative and executive branches of public authority on the one hand, and the judiciary on the other. Regarding this body, i.e., the judiciary council, they problematize not only external inadmissible influences or attacks on the independent judiciary, but also internal attacks (which are too often ignored, probably because they are less obvious and more difficult to recognize). In short, if the judiciary council is not properly structured and secured, it can have the character of a Trojan horse.
Keywords: Evropska unija; neodvisno sodstvo; sodniki; sodstvo